Socio-legal study of community pathology in the social space - Teguh Suratman; Wika Yudha Shanty (Faculty of Law, University of Merdeka Malang, 2022)
The human instinct to be better than others causes various deviations; the instinct for eating, power, sexuality, selfishness, Etc. Contributes to various forms of ignorance/deviations, which are called social diseases. Diseases of society are part of social life that is always present in society. Therefore, its existence is a common problem and requires a joint solution. Currently, people's awareness of social ills has diminished, so the condition is very alarming; as can be seen at every crossroads, there are many beggars, homeless people, and disabled people; it even happens in schoolsâ€”early childhood. Therefore, the concern of all levels of society is needed to be involved in solving and overcoming this problem. The problem of children at this time is not only a problem for families, society, and the nation, but it has also become a world problem, which also involves world institutions. Therefore, the problem of children today is a serious and global problem. For this reason, it is necessary to pay attention to all elements of society so that they take part in dealing with and alleviating these problems.How to cite item:Â Suratman, T., Shanty, W. (2022). Socio-legal study of community pathology in the social space.Â Jurnal Cakrawala Hukum, 13(3), 337-346. DOI:https://doi.org/10.26905/idjch.v13i3.8880.